Identification of Microplastics in Water Column at Koto Panjang Dam, Kampar Regency, Riau Province - Muhammad Edy; Budijono Budijono; Muhammad Hasbi (Berkala Perikanan Terubuk, 2021)
In PLTA Koto Panjang Dam, plastic waste comes from various community activities and fishery activities. The waste is destroyed into small particles (0.3-5mm) called microplastics. To determine the presence of microplastics in the water column, a study was conducted in December 2020 - February 2021. Water samples were taken from 3 stations with 3 sampling points at 3 different depths using Water Sampler. 250 ml of water was taken and filtered using a plankton net plankton no. 25. To obtain the microplastics, the filtered water was again filtered using Whatman filter paper No.42 and the type of microplastics were identified using a binocular microscope. The results of the study were found to be fiber, film and fragments. The abundance of microplastics ranged from 22 to 533.33 particles/m3. The highest total abundance is at station 3 with fiber type at a depth of 3 meters at 533.33 particles/m3. While the lowest abundance type is at station 1 with a film type at a depth of 6 m as many as 22 particles/m3.